FRI0059 Cardiac, pulmonary and periodontal disease as comorbidities in tnf-driven models of chronic polyarthritis. (15th June 2017) - Denis, MC; Ntari, L; Sakkou, M; Chouvardas, P; Prados, A; Consortium, GMC; Fuchs, H; Gailus-Durner, V; Angelis, M Hrabě de; Simic, B; Crucet, M; Lüscher, TF; et al.
Abstract : Background: Patients with RA exhibit an increased risk of developing multiple extraarticular pathologies. The link between co-manifested pathologies and RA at the level of common molecular and cellular mechanisms remains to be further elucidated. Objectives: We aimed to identify comorbidities developing in models of TNF-driven chronic polyarthritis and further explore their aetiopathogenesis. Methods: Through detailed phenotyping, clinical, histopathological and functional analysis we investigated the development of comorbidities in the Tg197 and Tnf ΔARE/+ mouse models that overexpress respectively human and mouse TNF and develop spontaneous chronic polyarthritis with the concomitant development of Crohn's-like IBD in the case of the Tnf ΔARE/+ animals. Targeting mesenchymal origin cells, ex vivo cellular analyses and RNA sequencing expression profiling allowed us to further explore the key cellular instigators of RA related comorbidities. Results: Histopathological evaluation and echocardiography assessment of both arthritis models showed thickening of the aortic valve and cardiac dysfunction characterized by mild decreased fractional shortening, decreased heart rate and increased velocities in ascending aorta hinting towards aortic valve disease. The aortic valve pathology, similarly to arthritis, was ameliorated with anti-TNF treatment. The thickening of the aortic valve leaflets was due to fibrosis which consisted almost entirely of mesenchymal origin Valve Interstitial Cells (VICs). VICs from mutant mice expressed high levels of TNF and exhibited a proliferative and migratory phenotype resembling the activated phenotype of pathogenic Synovial Fibroblasts (SFs) isolated from the joints of the same mice. RNA-seq analysis further supported a significant correlation between pathogenic SFs and VICs highlighting a common cellular mechanism linking RA and aortic valve pathology. Furthermore, we show that TNF deregulation leads to additional RA related comorbidities, as described in human disease, including periodontitis with early onset alveolar bone loss and pulmonary inflammation with mild to severe bronchus-associated lymphoid tissue (BALT). Conclusions: Similarly to human RA patients, TNF-driven arthritis models develop multiple RA-associated comorbidities, offering novel insights into potential molecular and cellular mechanisms commonly underlying these complex pathologies. References: Keffer, J. et al. Transgenic mice expressing human tumour necrosis factor: a predictive genetic model of arthritis. EMBO J. 10, 4025–4031 (1991). Kontoyiannis, D. et al. Impaired on/off regulation of TNF biosynthesis in mice lacking TNF AU-rich elements: implications for joint and gut-associated immunopathologies. Immunity 10, 387–398 (1999). Armaka, M. et al. Mesenchymal cell targeting by TNF as a common pathogenic principle in chronic inflammatory joint and intestinal diseases. J. Exp. Med. 205, 331–7 (2008). Disclosure of Interest: None declared